Geographical variation in antimicrobial use and multiresistant pathogens in Brazilian intensive care units: a nationwide study - Ramos Oliveira Silva, Alice; Xavier Borges Barbosa, Constanza; Soares Rebelo, Raianne; Fernandez-Llimos, Fernando; Costa Lima, Elisangela (The Journal of Infection in Developing Countries, 2023)
Introduction: Geographical analyses of antibiotic use identify regions with the highest consumption and help design policies for strategic patient groups. Methodology: We conducted a cross-sectional study based on official data available in July 2022 from Brazilian Health Surveillance Agency (Anvisa). Antibiotics are reported as a defined daily dose (DDD) per 1,000 patient-days, and central line-associated bloodstream infection (CLABSI) is defined according to Anvisa criteria. We also considered multi-drug resistant (MDR) as the critical pathogens the World Health Organization listed. We measured antimicrobial use and CLABSI trends per ICU bed using the compound annual growth rate (CAGR). Results: we evaluated the regional variation in CLABSI by multidrug-resistant pathogens and the antimicrobial use in 1,836 hospital intensive care units (ICUs). In 2020, the leader in use in intensive care units (ICUs) in the North was piperacillin/tazobactam (DDD = 929.7) in the Northeast. Midwest and South were meropenem (DDD = 809.4 and DDD = 688.1, respectively), and Southeast was ceftriaxone (DDD = 751.1). The North has reduced polymyxin use (91.1%), and ciprofloxacin increased (439%) in the South. There was an increase in CLABSI by carbapenem-resistant Pseudomonas aeruginosa in the North region (CAGR = 120.5%). Otherwise, CLABSI by vancomycin-resistant Enterococcus faecium (VRE) increased in all regions except the North (CAGR = -62.2%), while that carbapenem-resistant Acinetobacter baumannii increased in the Midwest (CAGR = 27.3%). Conclusions: we found heterogeneity in antimicrobial use patterns and CLABSI etiology among Brazilian ICUs. Although Gram-negative bacilli were the primary responsible agent, we observed a notable increase trend of CLABSI by VRE.